Co-design of “Baatcheet,” a peer-supported, web-based storytelling intervention for young people with common mental health problems in India - Pattie P. Gonsalves; Dhriti Mittal; Shruti Aluria; Aarushi Khan; Eshita Razdan; Priyambada Kashyap; Navvya Rahate; Manek D’Silva; Sonaksha Iyengar; Faith Gonsalves; Sweta Pal; Salik Ansari; et al. (Cambridge Prisms: Global Mental Health)
Abstract Background Engaging with personal mental health stories has the potential to help people with mental health difficulties by normalizing distressing experiences, imparting coping strategies and building hope. However, evidence-based mental health storytelling platforms are scarce, especially for young people in low-resource settings.